A extensão na Universidade Federal de Uberlândia: uma proposta avaliativa - Ferreira, Denilson Carrijo (2021)
In the present study, we researched Extension at the Federal University of Uberlândia (UFU) based on the analysis of the effects of the institution's first Extension Policy in the period from 2009 to 2019 and we proposed an instrument to assess Extension based on the national indicators proposed by the Forum of Extension Pro-rectors of Public Institutions of Higher Education in Brazil (FORPROEX). Initially, we approached the subject of University Extension from an international historical panorama, and then we focused on the legal bases and the Brazilian benchmarks. In the sequence, we present the discussions about the evaluation of the extension in the national perspective and the indicators proposed by FORPROEX from which we proposed an instrument of evaluation of the Extension at UFU. The methodological approach was qualitative, since we used the UFU case study to develop a descriptive research based on the content analysis of the material collected through bibliographic and documentary research, in addition to the data obtained from the university itself, via the Information Service at the Citizen, in order to discuss the movement of Extension in the institution in the period between 2009 and 2019. The results of the present study point to the difficulty found in institutionalizing the Extension, mainly in the period before 2009. We trace a history of Extension at UFU, presenting its legal frameworks, and identified FORPROEX documents as the main reference framework. Then, we will discuss the Extension movement at UFU in the period under review, by modality, city, units, knowledge areas, thematic areas and extension lines, pointing to an overall growth of 181% in the number of actions. The Health and Education areas concentrate 59% of the actions. Then, we identified the scope of the Extension Policy in the construction of regulations within the UFU. The analysis of the listed resolutions was carried out based on the markers Evaluation, University Management, Dialogical Interaction, Student Training, Inseparability Teaching-Research-Extension and Extension Curriculum, with emphasis on the creation of Extension Coordinations in Academic Units and Special Units of Teaching, similar to the Research and Teaching Coordinations, and the inclusion of the Extensionist Dimension in the calculation of the institution's budget distribution. Norms were also identified that deal with the extension curriculum / accreditation, considered the next challenge of Extension Management in Brazil. Finally, an evaluation instrument was proposed based on Extension Indicators, widely discussed in FORPROEX, aiming to enable comparative historical analyzes between Federal Institutions of Higher Education and with other time frames of UFU itself, subsidizing the implementation of improvements in the Management of University Extension . The application of this dissertation will enable managers to monitor the institutionalization and management of Extension at UFU, better direct financial resources and propose promotion programs focused on increasing actions in areas with less Extension activities, in order to equalize the development of activities in the most diverse areas.